2012
DOI: 10.1051/0004-6361/201219545
|View full text |Cite
|
Sign up to set email alerts
|

Herschel/HIFI observations of red supergiants and yellow hypergiants

Abstract: Context. Red supergiant stars (RSGs) and yellow hypergiant stars (YHGs) are believed to be the high-mass counterparts of stars in the asymptotic giant branch (AGB) and early post-AGB phases. As such, they are scarcer and the properties and evolution of their envelopes are still poorly understood. Aims. We study the mass-loss in the post main-sequence evolution of massive stars, through the properties of their envelopes in the intermediate and warm gas layers. These are the regions where the acceleration of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 38 publications
(47 reference statements)
3
58
0
Order By: Relevance
“…If N 2 is photodissociated faster than assumed in our chemical model (Bohlin et al 1978) the enhancement of nitrogen needed to fit the NO profiles would not be that high. Also, a detailed modeling of the line emission from H 2 O presented by Teyssier et al (2012) would help check that the abundance of this molecule is higher than what is assumed in the present work, which would result in lower nitrogen abundances. The model fitting is shown in Fig.…”
Section: Modelling the No Emissionmentioning
confidence: 64%
See 3 more Smart Citations
“…If N 2 is photodissociated faster than assumed in our chemical model (Bohlin et al 1978) the enhancement of nitrogen needed to fit the NO profiles would not be that high. Also, a detailed modeling of the line emission from H 2 O presented by Teyssier et al (2012) would help check that the abundance of this molecule is higher than what is assumed in the present work, which would result in lower nitrogen abundances. The model fitting is shown in Fig.…”
Section: Modelling the No Emissionmentioning
confidence: 64%
“…Recently, Teyssier et al (2012) have observed selected transitions of NH 3 , OH, H 2 O, CO, and 13 CO with HIFI towards this object. They also show that the model derived by Castro-Carrizo et al (2007) for low-J CO transitions was applicable, with minor changes, to higher excitation lines.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Bell et al 1980;Menten & Alcolea 1995), several (pre-)planetary nebulae (CRL 2688, OH 231.8+4.2, CRL 618) (Nguyen-Q-Rieu et al 1984;Morris et al 1987;Truong-Bach et al 1988, 1996Martin-Pintado & Bachiller 1992a,b;Martin-Pintado et al 1993, 1995, and the hypergiant IRC +10420 (Menten & Alcolea 1995). More recently, submillimetre observations with space observatories have detected rotational transitions of NH 3 from evolved stars of all chemical types, including the C-rich star IRC +10216 (C/O > 1; Hasegawa et al 2006;Schmidt et al 2016), several O-rich stars (C/O < 1; Menten et al 2010;Teyssier et al 2012), and the S-type star W Aquilae (C/O ≈ 1; Danilovich et al 2014).…”
Section: Introductionmentioning
confidence: 99%